NESTJS VS EXPRESS.JS: A COMPREHENSIVE COMPARISON - J.J. Munirov (Modern World Education: New Age Problems – New solutions, 2025)
This article explores the differences between Express.js and NestJS, two popular Node.js frameworks used for building server-side applications. Express.js is a minimalist, flexible framework known for its simplicity and lightweight approach, while NestJS is a robust, opinionated framework that incorporates modern architectural patterns like dependency injection and modularity. The article delves into their core features, use cases, benefits, and potential drawbacks, providing a clear understanding for developers seeking the best fit for their projects.